DETEKSI FINANCIAL STATEMENT FRAUD DENGAN MODEL BENEISH M-SCORE - KUSUMA INDAR PREHANTIKA, FERNANDA (Jurnal Akuntansi AKUNESA, 2016)
Abstact The purpose of study to examine the influence of model Beneish m-score to detection of fraud. Data used is secondary data that companies listed on the Indonesia Stock Exchange in 2011-2015. Samples were obtained through purposive sampling techniques, used as a sample of 580 companies listed on Bursa Efek Indonesia at 2011-2015. The independent variabel in the study was Receivable Days Sales Index, Gross Margin Index, Asset Quality Index, Grow Sales Index, Depreciation Index, general and administration Sales Index, Leverage Index, Total Accrual to Total Assets and dependent variable is fraud. Data analysis using logistic regression and the results showed that the Days Sales Receivable Index, Gross Margin Index, Asset Quality Index, Sales Grow Index, Leverage Index, Total Accrual to Total Asset affect the detection of fraud, while Depreciation Index and Sales general and administration Index does not affect the detection of fraud.